THE NATIONAL IDEA IS THE LEADING FORCE OF HUMANITY TOWARDS SUSTAINABLE DEVELOPMENT (Scientific journal of the Fergana State University, 2024)
This article reveals the scientific and philosophical significance of the issue of national ideology in ensuring the stability of society. At a new stage in the development of the national idea society, the need for a new rise in the transformation of the individualʼs worldview has been studied. It is scientifically based that the feature of the national idea in society in the rise of society is to ensure stability.